Physiologic response of six plant species grown in two contrasting soils and irrigated with brackish groundwater and RO concentrate. Issue 2 (3rd April 2017) - Flores, Alison M.; Shukla, Manoj K.; Schutte, Brian J.; Picchioni, Geno; Daniel, David
ABSTRACT: With declining availability of fresh surface water, brackish groundwater is increasingly used for irrigation in the arid and semi-arid southwestern United States. Brackish water can be desalinated by reverse osmosis (RO) but RO results in a highly saline concentrate. Disposal of concentrate is a major problem hindering augmentation of inland desalination in arid areas. The objective of this study was to determine the effect of texture and saline water irrigation on the physiology of six species ( Atriplex canescens (Pursh) Nutt., Hordeum vulgare L., Lepidium alyssoides A. Gray, Distichlis stricta (L.) Greene, Panicum virgatum L., and × Triticosecale Wittm. ex A. Camus [ Secale × Triticum ]). All species were grown in two contrasting soils and irrigated with the same volume of control water (EC 0.9 dS/m), brackish groundwater (4.1 dS/m), RO concentrate (EC 8.0 dS/m). Several plant physiological measurements were made during the growing season including height, number of stem nodes, average internodal length, number of leaves, leaf length, photosynthetic rates, stomatal conductance rates, transpiration rates, leaf temperatures, stem water potential, and osmotic potential. P. virgatum was the only species that showed significant decrease in plant height and growth with texture and irrigation water salinity. Except for A. canescens and L. alyssoides, number and length of leaves decreased with increasing salinity for all species. No significant differences were observed for photosynthetic, stomatal conductance, and transpiration rates by soil texture or irrigation water salinity. Stem water potential and osmotic potential did show some significant influence by soil texture and irrigation water salinity. Based on the results, RO concentrate can be reused to grow all six species in sand; however, growth of all species showed some limitations in clay. Local reuse of RO concentrate along desert margins with regular soil and environmental quality monitoring can accelerate implementation of inland desalination for sustaining food security.